A roadmap for a comprehensive control of cervical cancer in Poland: integration of available solutions into current practice in primary and secondary prevention. Issue 2 (March 2020) - Nowakowski, Andrzej; Arbyn, Marc; Turkot, Maryla H.; Wieszczy, Paulina; Miłosz, Kinga; Kamiński, Michał F.; Didkowska, Joanna; Bidziński, Mariusz; Olszewski, Włodzimierz; Wielgoś, Mirosław; Krzakowski, Maciej; Kuchar, Ernest; et al.
Abstract : In Poland, cervical cancer incidence and mortality still remain considerably higher than in Western European countries or North America. Recent data indicate decreasing trends in women younger than 60 years and stable trends in older women. In this article, we identified obstacles in primary and secondary prevention of cervical cancer in Poland. We analysed local legislation, management structure and organization of cervical cancer prevention in Poland and reviewed solutions available and implemented in other European countries. The main weaknesses include: (i) very low coverage of organized screening; concurrent unregistered opportunistic screening with unknown coverage and high test consumption (ii) suboptimal quality assurance in organized screening and no external quality assurance in opportunistic screening (iii) very low coverage of human papillomavirus vaccination that is not centrally reimbursed (iv) absence of pilot evaluation of (a) interventions that may improve population coverage and (b) performance of new preventive strategies. The proposed solutions are multifaceted and involve: (i) legislative and organizational regulation of cervical cancer screening aimed at comprehensive registration of procedures, data access and quality assurance (ii) pilot testing and implementation of new ways to increase coverage of cervical cancer screening, in particular among older women (iii) pilot evaluation with possible introduction of human papillomavirus-based screening and (iv) inclusion of human papillomavirus vaccination into the reimbursed national immunization program.